Variation in vitamin E level and aflatoxins contamination in different rice varieties - Iqbal, Shahzad Zafar; Mustafa, Hafiz Ghulam; Asi, Muhammad Rafique; Selamat, Jinap (Elsevier, 2014)
In the present study, a total of 380 samples of 5 rice varieties were investigated for the presence of aflatoxins (AFs) and tocopherols (Vitamin E) using HPLC, equipped with a fluorescence detector. The data revealed that super basmati rice has the highest mean level of total AFs (12.45 μg/kg) followed by KS-282 (11.2 μg/kg), basmati PK-385 (9.8 μg/kg), Irri-6 (9.7 μg/kg) and the lowest mean level was found in Irri-9 (8.9 μg/kg). Furthermore, the results have shown that the variety with lowest level of AFs has the highest level of tocopherol content; i.e. Irri-9 (53.2 mg/100 g), basmati PK-385 (45.9 mg/100 g), Irri-6 (45.3 mg/100 g), KS-282 (40.4 mg/100 g) and super basmati rice (40.2 mg/100 g). The data has shown correlation (r = −0.62, p < 0.05) between vitamin E content and AFs concentration in different rice varieties. The results are interesting and need further study to investigate the mechanistic background of vitamin E content and its effect on aflatoxins contamination.